Circular Economy and Opportunities for Small and Medium Enterprises in Lather Industry of Sialkot Pakistan - Zain Ul Abidin; Rabia Qammar; Fozia Latif Gill (Journal of Business and Social Review in Emerging Economies, 2023)
Purpose: The purpose of this study is to find the opportunities/ benefits and barriers for the implementation of circular economy in lather manufacturing small and medium enterprises in Sialkot Pakistan.